2008
DOI: 10.1182/blood-2007-03-081554
|View full text |Cite
|
Sign up to set email alerts
|

Junctional adhesion molecule-A, JAM-A, is a novel cell-surface marker for long-term repopulating hematopoietic stem cells

Abstract: Junctional adhesion molecule-A (JAM-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 48 publications
2
45
1
Order By: Relevance
“…Sugano et al showed that F11r was strongly expressed in the enriched HSC fraction in murine bone marrow, fetal liver, and aorta-gonad-mesonephros, and that F11r is an excellent marker for isolating HSCs. 34 These observations suggest that F11r plays important roles in the adhesion and interaction between HSCs and their niches.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sugano et al showed that F11r was strongly expressed in the enriched HSC fraction in murine bone marrow, fetal liver, and aorta-gonad-mesonephros, and that F11r is an excellent marker for isolating HSCs. 34 These observations suggest that F11r plays important roles in the adhesion and interaction between HSCs and their niches.…”
Section: Discussionmentioning
confidence: 93%
“…30 (4) f11r (F11 receptor; also known as junctional adhesion molecule-A): F11r is a cell adhesion molecule with 2 immunoglobulin-like domains and is localized at a tight junction of epithelial, endothelial, and hematopoietic cells. [31][32][33][34] Although its role in hematopoiesis is unclear, F11r is known to play a role in the adhesion of blood cells to endothelial cells. 35 (5) 36 However, the role of Krt18 in hematopoiesis is still unknown.…”
Section: Validation Of Microarray Results By Rt-pcr and In Situ Hybrimentioning
confidence: 99%
“…10 Recently, expression of several JAM family members, such as JAM-A, JAM-C, JAM4, or ESAM, has been reported in hematopoietic stem cells (HSCs), although a function for these proteins in hematopoiesis remains unknown. [11][12][13][14][15][16] In adult mammals, HSCs are rare cells mainly located in the bone marrow (BM) and able to generate all mature blood cells. In mice, HSCs are comprised within the LSK compartment as defined by the Lineage Neg c-kit Hi Sca-1 Hi (LSK) phenotype; the LSK compartment can be further subdivided using additional markers such as CD34, CD150, or CD48.…”
Section: Introductionmentioning
confidence: 99%
“…in the bone marrow, with their expression decreasing during the acquisition of a more differentiated state (Nagamatsu et al, 2006;Sakaguchi et al, 2006;Sugano et al, 2008;Praetor et al, 2009). Furthermore JAM-A expression has been reported to be high on undifferentiated HC11 mammary epithelial cells relative to differentiated cells (Perotti et al, 2009).…”
Section: J a M -A J A M -B J A M -C A N D J A M -4 H A V E B E E mentioning
confidence: 99%